A Critical Perspective of the Unique Selling Point for Sustainable Tourism Development: Pentingsari Tourism Villag - Raden Rucitarahma Ristiawan (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2019)
The proliferation of community-based tourism village development in Indonesia context promises an ideal model of alternative tourism that puts its main central concern in empowering community. This model could also escalate the community participation and emancipation in their development process through enabling tourism activities surround their area. However, the raising numbers of community-based tourism villages that mostly appear with similar product characteristic and unique selling point, for example in Yogyakarta, Indonesia, has also encouraged challenges in terms of product competition and development. This study aims at identifying the potentials and challenges of the Unique Selling Point of Pentingsari Tourism Village through enabling sustainable tourism product development and marketing lens. Through employing a qualitative case study approach, the data gathered mostly through observation and interview with local community tourism organization members. The findings show that to some extent, sustainable tourism village development paradigm can also encourage the unsustainable practices of tourism development if the paradigm is only be applied partially in a tourism village site.